"It Looks Like a Demon": Black Masculinity and Spirituality in the Age of Ferguson. Issue 2 (June 2016) - Hawley, Jamie D.; Flint, Staycie L.
In this commentary, we contribute to the broader men's studies research and thought with particular focus on the Black male experience locating Black masculinity and Black spiritual identity as the potential site of trauma and soul murder through the saga of Ferguson, Missouri and the Mike Brown murder of 2014.